2017
DOI: 10.1111/sms.12844
|View full text |Cite
|
Sign up to set email alerts
|

Do post‐concussion‐like symptom responses change following exercise or sports participation in a non‐concussed cohort?

Abstract: The purposes of this study were (a) to determine the reliable change in post-concussion-like symptoms reported following self-selected exercise or sports activities and (b) to explore the potential influence of gender and exercise parameters on post-concussion-like symptoms reported by a non-concussed cohort following exercise/training. A pre-to-post observational design was used. A convenience sample of students aged 18-30 years who visited a university recreation center to engage in their chosen exercise act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This is because previous studies have demonstrated that exercise provokes and increases symptoms in individuals with a concussion5 and in non-concussed participants 6…”
Section: Discussionmentioning
confidence: 99%
“…This is because previous studies have demonstrated that exercise provokes and increases symptoms in individuals with a concussion5 and in non-concussed participants 6…”
Section: Discussionmentioning
confidence: 99%
“…Participants may have independently engaged in physical activity before testing, which can negatively affect performance on the SCAT5. [46][47][48] To mitigate this, participants were requested to not engage in physical activity immediately before testing sessions. Testing sessions were scheduled at the beginning of regular sport participation sessions or on nonparticipation days for respective sports to mitigate the potential effect of physical activity.…”
Section: Limitationsmentioning
confidence: 99%